Academic Staff Associations and Vaccination Mandates in the Canadian University Sector - Braley-Rattai, Alison; Savage, Larry (Relations industrielles / Industrial Relations, 2024)
SummaryNo COVID-19 mitigation measure has proven more controversial than vaccination mandates. While the prospect of widespread vaccination in 2021 offered hope for a return to pre-pandemic normalcy on Canadian university campuses, proposals for on-campus vaccination mandates sparked intense debate and led to varying approaches at universities.We examine the pivotal role of academic staff associations (ASAs) in advocating and influencing the adoption of vaccination mandates at Canadian universities in the run-up to the fall 2021 term. Through document analysis and semi-structured interviews with ASA leaders and staff, we delve into the factors behind ASA positions on such mandates.Although the vast majority of ASAs advocated robust COVID-19 mitigation measures, including vaccination mandates, their approaches varied because of regional differences and institutional and sectoral dynamics. Many ASAs actively promoted mandatory vaccination, unlike the case with the vast majority of other unions.We argue that ASAs played a crucial role in shaping university responses to the pandemic. Their advocacy contributed to widespread adoption of vaccination mandates before the fall 2021 term. We stress the importance of understanding the nuanced responses of ASAs to such mandates, while shedding light on the interplay of factors behind ASA positions. AbstractWe examine the pivotal role of academic staff associations (ASAs) in advocating and influencing the adoption of vaccination mandates at Canadian universities in the run-up to the fall 2021 term. Through document analysis and semi-structured interviews with ASA leaders and staff, we delve into the factors behind ASA positions on such mandates. We demonstrate that the vast majority of ASAs advocated robust COVID-19 mitigation measures, including vaccination mandates, but their approaches varied because of regional differences and institutional and sectoral dynamics. Many ASAs actively promoted mandatory vaccination, unlike the case with the vast majority of other unions.